2011
DOI: 10.2215/cjn.11261210
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers and Renal Recovery in Critically Ill Patients with Renal Support

Abstract: SummaryBackground and objectives Despite significant advances in the epidemiology of acute kidney injury (AKI), prognostication remains a major clinical challenge. Unfortunately, no reliable method to predict renal recovery exists. The discovery of biomarkers to aid in clinical risk prediction for recovery after AKI would represent a significant advance over current practice.Design, setting, participants, & measurements We conducted the Biological Markers of Recovery for the Kidney study as an ancillary to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
149
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 34 publications
5
149
1
3
Order By: Relevance
“…Modest increases in urinary NGAL have also been detected in patients with prerenal AKI, suggesting that mild renal tubular injury could be recognized (31). Decreasing urinary NGAL was associated with greater odds for renal recovery (32). However, sCr and GFR achieved similar performance levels, and both plasma and urinary NGAL had only a minor role in predicting hospital mortality (31).…”
Section: Discussionmentioning
confidence: 99%
“…Modest increases in urinary NGAL have also been detected in patients with prerenal AKI, suggesting that mild renal tubular injury could be recognized (31). Decreasing urinary NGAL was associated with greater odds for renal recovery (32). However, sCr and GFR achieved similar performance levels, and both plasma and urinary NGAL had only a minor role in predicting hospital mortality (31).…”
Section: Discussionmentioning
confidence: 99%
“…First, we selected candidate biomarkers on the basis of biologic plausibility within inflammation and apoptosis. We did not include more recent novel urinary biomarkers, such as neutrophil gelatinase-associated lipocalin (14), kidney injury molecule-1 (15), or cell-cycle arrest markers (16,17) because the ATN trial did not collect urine samples (3). In a small subset of the BioMaRK study cohort, we previously examined a panel of urinary markers and found that day 1 results were of similar predictive value (AUROC, 0.51-0.66) to the markers examined in this study (15).…”
Section: Discussionmentioning
confidence: 99%
“…La utilización de biomarcadores asociados a IRA, como son la Lipocalina Asociada a Gelatinasa de Neutrófilos (NGAL), cistatina C, IL-18 y KIM-1, para diagnóstico precoz, podría ayudar a mejorar el pronóstico que no ha cambiado en los últimos años. Hasta el día de hoy no se ha logrado que los biomarcadores constituyan una herramienta útil en la práctica clínica [42][43][44][45][46] , estableciéndose así un desafío a futuras investigaciones.…”
Section: Discussionunclassified